In-vitro Antimicrobial Activity and Phytochemical Screening of Fritillaria delavayi - Maharjan, Bijaya L; Devkota, Hari K; Baral, Bikash (Nepal Journal of Science and Technology, 2012)
Fritillaria delavayi Franch is one of the medicinal plants used in traditional medical system for ailment of various diseases. But scientific study of the plant has been less carried out for which the study was conducted for validation of prevailing medical practice. The soxhlet extraction of the bulbs of plant were conducted in various solvents (hexane, chloroform, ethyl acetate, methanol and water) differing in polarity. Maximum yield (6.79%) was obtained in aqueous fraction and lowest (0.14%) in ethyl acetate fraction. The phytochemical screening of extracts revealed the presence of volatile oil, glycosides, sterol and triterpenes, polyoses, saponins, reducing compounds, quinones, flavonic glycosides and coumarins. In antimicrobial assay conducted by agar well diffusion method, chloroform fraction was found to be more effective towards bacterial and fungal pathogens tested, followed by ethyl acetate and methanol fraction. The hexane and aqueous fractions were found to be least effective against all the tested pathogens. Among the bacterial pathogens, maximum inhibition zone was depicted against Klebsiella pneumoniae (22 mm) by chloroform extracts while among the fungal pathogens, greatest inhibition activity was observed against Fusarium moniliforme (19 mm). The antimicrobial activity of extracts suggested potential use of the plant in treatment of various diseases. DOI: http://dx.doi.org/10.3126/njst.v12i0.6484 Nepal Journal of Science and Technology 12 (2011) 85-90